Comparative Analysis of Platelet-to-Lymphocyte Ratio and Neutrophil-to-Platelet Ratio as Diagnostic Markers in Dengue and Malaria: Comparative Analysis of Platelet-to-Lymphocyte Ratio and Neutrophil-to-Platelet Ratio - Naz, Sehreen; Ujjan, Ikram Din; Majeed, Sadia; Ghani, Abdul; Khaksheli, Sughand; Rajput, Asma (Pakistan Journal of Health Sciences, 2025)
Dengue fever and malaria are endemic febrile illnesses in South Asia that often present with overlapping clinical features. Accurate differentiation is essential for timely and appropriate treatment. Inflammatory biomarkers such as the Platelet-to-Lymphocyte Ratio (PLR) and Neutrophil-to-Platelet Ratio (NPR) may aid diagnostic decision-making. Objectives: To evaluate the role of PLR and NPR as diagnostic markers in distinguishing dengue fever from malaria in patients presenting with acute febrile illness. Methods: A cross-sectional comparative study was conducted at LUMHS, Hyderabad, over 6 months. A total of 116 patients (58 each with confirmed dengue and malaria) were enrolled using non-probability consecutive sampling. Clinical data and complete blood counts were collected. PLR and NPR were calculated and analyzed for diagnostic accuracy using SPSS version 21.0. ROC curve analysis determined optimal cutoffs, sensitivity, and specificity. Results: The mean PLR was significantly lower in dengue (109.7 ± 58.2) compared to malaria (131.6 ± 69.3) (p=0.034). NPR did not show a significant intergroup difference (p=0.321). At a cutoff of 73.89, PLR demonstrated moderate sensitivity (65.52%) and low specificity (36.21%). NPR showed high specificity (100%) but no sensitivity (0%) at a cutoff of 0.0500. Conclusions: PLR can be considered a modestly useful marker in differentiating dengue from malaria, while NPR lacks diagnostic sensitivity. These findings suggest that PLR, in conjunction with clinical evaluation, may support early differentiation between the two diseases.